"Doing the devil's work": Emotional labour and stigma in expanding Needle and Syringe Programs. (3rd September 2015) - Treloar, Carla; Hopwood, Max; Yates, Kenneth; Mao, Limin
Abstract: Expansion of Needle and Syringe Programs (NSPs) to non-specialised sites requires an NSP workforce with skills in engaging stakeholders who may have different opinions of NSP. This study examined the strategies used by NSP workers to develop and maintain NSP services and the emotional labour involved in performing this work. Qualitative interviews were undertaken with 12 staff of a NSP network in metropolitan Sydney, Australia. Participants had undertaken a range of activities to expand NSP sites, often in unwelcoming environments in which NSP was viewed as a "cowboy" service. Participants' strategies included building positive, ongoing inter-group contact, being visible in external services, and maintaining their professionalism to promote NSP as a legitimate service and themselves as legitimate health workers. Some participants employed strategies which were at odds with their personal and professional values. Participants relied on cohesion within the NSP team to support and encourage each other. Dealing with external services to establish and maintain NSPs was a source of significant emotional labour for NSP workers and was grounded in the stigma attached to injecting drug use. NSP policies and procedures should account for this additional work undertaken by NSP staff and leadership is required to address stigmatisation of NSPs.